1870 Tex. Gen. Laws 63, ch. 46, § 1; An Act Regulating the Right to Keep and Bear Arms, Aug. 12, 1870, reprinted in 2 A Digest of the Laws of Texas: Containing the Laws in Force, and the Repealed Laws on Which Rights Rest from 1864 to 1872, at 1322 (George W. Paschal 1873) - (:unkn) unknown (My University, 1870)
Banned carry of any bowie-knife, dirk, or butcher-knife, or firearms,whether known as a six-shooter, gun, or pistol of any kind at any church or religious assembly, any school-room or other place where persons are assembled for educational, literary, or scientific purposes, or into a ball room,social party, or other social gathering, composed of ladies and gentleman, or to any election precinct on the day or days of any election, where any portion of the people of this state are collected to vote at any election, or to any other place where people may be assembled to muster or to perform any other public duty, or any other public assembly
Keywords: CARRY - CERTAIN PUBLIC PLACES